A Case of REM Sleep Behavior Disorder, Narcolepsy-Cataplexy, Parkinsonism, and Rheumatoid Arthritis. (18th February 2014) - Cosentino, Filomena I. I.; Distefano, Angela; Plazzi, Giuseppe; Schenck, Carlos H.; Ferri, Raffaele
Abstract : A patient is reported in whom signs and symptoms of REM sleep behavior disorder (RBD) and narcolepsy have been associated for almost two decades with a late development of parkinsonism and rheumatoid arthritis. A 78-year-old male patient in whom RBD was first diagnosed was followed-up by clinical examination, video-polysomnography, multiple sleep latency test, cerebral magnetic resonance imaging, and dopamine transporter imaging by single-photon emission computerized tomography. The patient was found to present for almost two decades, in addition to RBD, also narcolepsy. Moreover, a late development of parkinsonism and the occurrence of rheumatoid arthritis were detected and clinically and instrumentally characterized. Patients predisposed to RBD and later parkinsonism might be susceptible to a variety of triggers that, in our patient, might have been represented by a possible latent autoimmune process leading to the development of narcolepsy with cataplexy and rheumatoid arthritis, later.